A Stock-Flow Accounting Model of the Labor Market : An Application to Israel - Yakhin, Yossi (IMF Working Papers; Working Paper ;, 2015)
The paper utilizes a theoretical stock-flow accounting model of the labor market, similar to Blanchard and Diamond (1989). Identifying restrictions are derived from the theoretical model and are imposed on a SVAR system. The estimation allows for decomposing fluctuations to their cyclical and structural components. The model is applied to the Israeli economy. The estimates suggest that non-cyclical factors account for at least half of the decline of the unemployment rate during the period between 2004-Q1, when unemployment peaked at 10.9 percent, and 2011-Q4, when it marked a trough at 5.4 percent; suggesting a shift inward of the Beveridge curve.